Movement patterns of a Critically Endangered elasmobranch (Dipturus intermedius) in a Marine Protected Area. Issue 2 (5th December 2021) - Lavender, Edward; Aleynik, Dmitry; Dodd, Jane; Illian, Janine; James, Mark; Wright, Peter J.; Smout, Sophie; Thorburn, James
Abstract: Marine Protected Areas (MPAs) are widely used in marine management, but for mobile species understanding the spatio‐temporal scale of management measures that is required to deliver conservation benefits depends on a detailed knowledge of species' movements that is often lacking. This is especially the case for species of skate (Rajidae) for which relatively few movement studies have been conducted. In Scotland, the Loch Sunart to the Sound of Jura MPA covering 741 km 2 has been designated for the conservation of the Critically Endangered flapper skate ( Dipturus intermedius ), but fine‐scale movements within this area remain poorly understood. A passive acoustic telemetry study which coupled acoustic tagging of 42 individuals and a static array of 58 receivers was conducted from March 2016 to June 2017. Using acoustic detection time series, angler capture–recapture data and depth time series from archival tags, fine‐scale movements of individuals were investigated. Overall, 33 of the 42 tagged individuals were detected. Residency, site fidelity and transiency were documented. Residency around receivers, lasting from 3 to more than 12 months, was documented in 16 acoustically detected individuals (48%) and all life‐history categories, but was most noticeable among females. Acoustic detections were associated with depth, salinity and season, but there was no evidence that individuals formed close‐knit groups in the areas in which they were detected. Taken together with historical occurrence records of flapper skate, the prevalence and scale of residency documented here suggest that the MPA is sufficiently large to benefit a notable percentage (38 [24–52]%) of skate found in the study area over monthly and seasonal timescales. This result strengthens the case for the use of MPAs to support the conservation of flapper skate and other skate species that display similar movement patterns in areas of high local abundance.